THE APPLICATION OF "SUBLIME BASED ON LEGAWA" IN ECONOMICS CLASS STUDENTS MAN 1 BANDA ACEH - Aprullah, Muhammad Putra; Sari, Rosalia; Sayuthi, Muhammad (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
This paper aims to improve the achievement of economics science olympiad students of MAN 1 Banda Aceh by implementing a spiritual blended learning method (sublime) based on legawa (lembaran penyangga jiwa). The spiritual blended learning method is a method that integrates religious and spiritual values ​​in a combination of face-to-face learning methods, online learning, and independent learning method. Legawa (lembaran penyangga jiwa) controls the implementation of religious and spiritual activities in face-to-face learning, independent learning, and online learning. The implementation of this method carries out documents and guidance on strengthening religious and spiritual activities as part of blended learning activities.  This method trains students to build self-controlling, patience, sincerity, gratitude, and peace of mind, increase self-confidence, critical thinking, collaboration, communication, innovation, and creative that presented on Unit Kegiatan Belajar Mandiri (UKBM) and digital media, such as Zoom, Google Meet, Quizizz, Kahoot, and online competition website. Developing character becomes the foundation for building students' motivation and self-awareness in learning and competing. Directly or indirectly, increasing students' motivation and self-awareness in learning and competing will have an impact on increasing the achievement of the Economics science olympiad’s students of MAN 1 Banda Aceh, which involves 20 students. From 2021 to 2023, the achievement of students has increased. The students have been rewarded 31 awards at the national level, seven at Aceh’s province level, and eight at the Banda Aceh level. Implementing the spiritual blended learning method (sublime) based on legawa (lembaran penyangga jiwa) in the economic science olympiad’s learning is in line with the implementation of religious moderation on the innovative MAN 1 Banda Aceh’s curriculum.